2022
DOI: 10.1177/03946320221123164
|View full text |Cite
|
Sign up to set email alerts
|

A new indicator: The diagnostic value of CD8+T/B lymphocyte ratio in sepsis progression

Abstract: Objective To reveal the value of single lymphocyte subpopulation and their ratios in the progression of sepsis. Methods From January 2019 to March 2021, 39 sepsis patients, 16 septic shock patients, and 50 healthy volunteers were recruited in the Second Xiangya Hospital for this cross-sectional study. The absolute quantitation of CD4+T, CD8+T, B lymphocytes, and NK cells in peripheral blood were determined by flow cytometry. SPSS Software was used to analyze the results. Results On the whole, the numbers of ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
1
1
0
1
Order By: Relevance
“…The reported results regarding the changes of CD8 cells in septic shock are controversial. As in the present results, the CD8 cells decrease in septic shock is the finding of one study (39), but according to another study, the percentage of CD8+T lymphocytes in the septic shock group was slightly higher than that in the sepsis group (40).…”
Section: Discussionsupporting
confidence: 74%
“…The reported results regarding the changes of CD8 cells in septic shock are controversial. As in the present results, the CD8 cells decrease in septic shock is the finding of one study (39), but according to another study, the percentage of CD8+T lymphocytes in the septic shock group was slightly higher than that in the sepsis group (40).…”
Section: Discussionsupporting
confidence: 74%
“…Peng и др. [16] обнаружили, что соотношение CD8 + T-лимфоциты/B-лимфоциты может быть использовано для диагностики прогрессирования сепсиса -с чувствительностью и специфичностью 75.00 и 71.79% соответственно -и для оценки эффекта проводимой терапии.…”
Section: клетки кровиunclassified
“…Li et al [15] reported that as sepsis progressed, CD3 + , CD4 + , and CD4 + /CD8 + counts in the blood of patients decreased, while elevated CD4 + and CD4 + /CD8 + counts correlated with patient recovery dynamics. Peng et al [16] found that the CD8 + T lymphocyte/B lymphocyte ratio can help diagnose the progress of sepsis (with sensitivity and specificity of 75.00% and 71.79%, respectively) as well as to assess the effect of the ongoing therapy.…”
Section: Blood Cellsmentioning
confidence: 99%